2020
DOI: 10.1002/jia2.25460
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of loss to follow‐up: incidence and associated factors in a cohort of HIV‐positive adults in rural Tanzania

Abstract: Introduction Lifelong antiretroviral therapy (ART) improves health outcomes for HIV‐positive individuals, but is jeopardized by irregular clinic attendance and hence poor adherence. Loss to follow‐up (LTFU) is typically defined retrospectively but this may lead to biased inferences. We assessed incidence of and factors associated with LTFU, prospectively and accounting for recurrent LTFU episodes, in the Kilombero and Ulanga Antiretroviral Cohort (KIULARCO) of HIV‐positive persons in rural Tanzania. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 42 publications
9
21
0
Order By: Relevance
“…Previous studies reported that travel distance to ART centers was a barrier to accessing treatment, and some mentioned transportation cost as a reason for defaulting. A similar study revealed that a substantial proportion of participants that lived far from the clinic (31% >50 km) was associated with a higher risk of LTFU [34]. Accessibility problems such as lack of transport, cost, or distance have previously been identified as barriers to clinic attendance.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies reported that travel distance to ART centers was a barrier to accessing treatment, and some mentioned transportation cost as a reason for defaulting. A similar study revealed that a substantial proportion of participants that lived far from the clinic (31% >50 km) was associated with a higher risk of LTFU [34]. Accessibility problems such as lack of transport, cost, or distance have previously been identified as barriers to clinic attendance.…”
Section: Discussionmentioning
confidence: 88%
“…4 10 11 Evidence shows that undernutrition significantly increases the risk of LTUF among adults living with HIV. [42][43][44][45][46][47] Therefore, understanding the impact of undernutrition on LTFU is essential in designing appropriate interventions. However, there is no systematic review and metaanalysis summarising available evidence about the pooled effect of undernutrition on LTFU among adults living with HIV in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] Studies have shown that undernutrition (ie, BMI <18.5 kg/m 2 ) is one of the main factors that significantly increases the risk of LTFU among adults living with HIV. [42][43][44][45][46][47] This finding may reflect that undernourished patients are more likely to develop OIs and later died but were under-reported to the HIV clinics due to a passive reporting system. 48 For example, a meta-analysis in SSA conducted by our team found that the risk of developing TB in undernourished adults living with HIV is twice that of well-nourished counterparts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Data linkage with other social services databases may also reduce the risk of IIT. In a recent cohort study, interventions that included longer periods between ART refills (i.e., multi-month dispensation), home delivery of ART refills, linkage to social service support programs after diagnosis, and “silent” transfer of care between clinics for patients relocating (e.g., due to change in employment) were all possible successful strategies for increasing retention in care and preventing the potential for therapy interruption [ 28 ].…”
Section: Discussionmentioning
confidence: 99%